2010
DOI: 10.1590/s0066-782x2010005000049
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de obesidade abdominal em hipertensos cadastrados em uma Unidade de Saúde da Família

Abstract: Background: Abdominal obesity is an important cardiovascular risk factor and, along with dyslipidemia, impaired glucose tolerance and hypertension, it makes up the metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
18

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 37 publications
(50 reference statements)
0
8
0
18
Order By: Relevance
“…(8) Studies have shown that smoking can simultaneously affect lipoprotein lipase activity and increase cortisol levels, leading to accumulation of fat in the abdominal adipocytes. (8,16) In comparison with total adiposity, central adiposity is more strongly associated with outcomes such as dyslipidemia, (20) hypertension, (17) and diabetes mellitus. (27) When the association between smoking and body fat distribution is investigated, there is a need to control potential confounders, especially alcohol consumption, which has a direct relationship with smoking (28) and has been suggested as a strong predictor of abdominal fat.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(8) Studies have shown that smoking can simultaneously affect lipoprotein lipase activity and increase cortisol levels, leading to accumulation of fat in the abdominal adipocytes. (8,16) In comparison with total adiposity, central adiposity is more strongly associated with outcomes such as dyslipidemia, (20) hypertension, (17) and diabetes mellitus. (27) When the association between smoking and body fat distribution is investigated, there is a need to control potential confounders, especially alcohol consumption, which has a direct relationship with smoking (28) and has been suggested as a strong predictor of abdominal fat.…”
Section: Resultsmentioning
confidence: 99%
“…(8) The prevalence of smoking remains high and the occurrence of obesity in the population is increasing, contributing to a significant increase in the incidence of cardiovascular disease. (17) The objective of the present study was to assess the independent association between smoking and anthropometric indicators of abdominal obesity, the association having been controlled for potential confounding factors.…”
Section: Introductionmentioning
confidence: 99%
“…11 Recently, studies have demonstrated the severe characteristic of an increased abdominal circumference, as it represents a risk for the development of chronic non-transmissible diseases, among which cardiovascular diseases stand out. [31][32] Regarding sedentary lifestyle, this variable was expected to present some association with obesity or hypertension, however, as it regards a subjective item, in other words, patients only answered if they practiced or not some physical activity, it was not possible to verify this information or measure it, nor the frequency in which patients practiced these activities.…”
mentioning
confidence: 99%
“…A elevada prevalência de OA em idosos corrobora com estudos desenvolvidos nos estados do Paraná 25 e Espírito Santo 26 , assim como na Espanha 27 . Verificou-se que o valor médio da CA foi diferente entre os gêneros, o que se assemelha com resultados de estudos nacionais 25,26 e internacionais 27,28 .…”
Section: Discussionunclassified
“…Verificou-se que o valor médio da CA foi diferente entre os gêneros, o que se assemelha com resultados de estudos nacionais 25,26 e internacionais 27,28 . Destaca-se que essa é a primeira pesquisa a analisar obesidade abdominal em idosos residentes na Região Centro-oeste do Brasil, assim contribui com informações sobre o problema da OA em idosos com perfil socioeconômico e epidemiológico difere das regiões sul e sudeste, onde as pesquisas populacionais com idosos foram realizadas.…”
Section: Discussionunclassified